Mechanism of generation and propagation characteristics of coastal trapped waves in the Black Sea - M. Aydın; Ş. T. Beşiktepe (Ocean Science, 2022)
Coastal trapped waves (CTW) are a major mechanism to distribute energy from the atmosphere in the ocean and play a significant role in large-scale, low-frequency sea-level and current variability in continental shelf and slope areas. Despite their significance for coastal dynamics, observational evidence of the influence of CTWs on the large-scale circulation is rather limited. In this study, mode-1 coastal trapped waves that were captured at sea-level stations at five locations along the southern coast of the Black Sea are examined together with sea surface height reanalysis from the Copernicus Marine Service to reveal their generation mechanisms and role in the coastal dynamics. It is found that the CTWs were formed when water accumulated on the western shelf after gale-force alongshore winds in the western Black Sea. Excited waves propagate along the Black Sea coast from west to east with a speed of 2.3–2.6 m s−1 and transport the atmospherically induced energy all over the Black Sea. The coastal current generated by the CTWs (on the order of 1 m s−1 in magnitude) and the main Black Sea current merge and flow eastward as a single structure, resulting in intensification of the Black Sea circulation during winter. Hence, we present evidence of the influence of CTWs on the large-scale circulation.